Une intervention en centres d’hébergement et de soins de longue durée visant à réduire les problèmes de santé mentale liés au travail - Renée Bourbonnais; Nathalie Gauthier; Michel Vézina; Chantal Viens; Pierre Durand; Chantal Brisson; Marie Alderson; Pauline Bégin; Jean-Paul Ouellet (Perspectives Interdisciplinaires sur le Travail et la Santé)
An intervention aimed at reducing adverse occupational psychosocial factors and their mental health effects was begun during the winter of 2002. This intervention can be summarized in five steps: commitment of stakeholders and setting up of an intervention team, identification of adverse occupational psychosocial factors, development of an action plan, implementation of the action plans, and evaluation of the intervention. The study was conducted in twelve residential and extended care centres (CHSLD) and included all care-giving staff in direct contact with patients (N= 493). A quasi-experimental design was used with four experimental groups and eight control groups, and with pre- and post-intervention measurements.The description of the intervention’s development and implementation phases and the evaluation at 12 months of the effects of the intervention on the prevalence of occupational psychosocial factors and mental health problems are presented.